Integrales orbitales nilpotentes et endoscopie pour les groupes classiques non ramifies - Waldspurger Jean-Loup (Paris Societe Mathematique de France, 2001)
This paper deals with Nilpotent orbital integrals and endoscopy for unramified classical groups.The paper contains also related results: a ``Lusztig function'' is equal to its Fourier transform up to a scalar and describes the scalar; and also the transfe
Keywords: Lie algebras; Nilpotent sets